(untitled) (Economic and Political Thought, 2014)
There is a growing empirical literature investigating the relationship between innovation activities of the firms and their ‘performance’. These firm-level studies usually employ Heckmann’s methodology and go under the name of CDM models (after the initials of the authors of the classical 1998 paper: Crepon, Duguet and Mairesse). The outcome of these studies is that firms that innovate more usually perform better, but there is a considerable variation when it comes to the details of the results. The aim of this paper is to contribute to the methodology of such literature, firstly, by discussing the theoretical foundations of the CDM models and thus shedding more light on the hypotheses underlying them, and secondly by assessing the usefulness of the Community Innovation Survey (CIS) in this respect. Several theoretical approaches are invoked, including neoclassical economics, Porter’s framework and evolutionary economics. It is argued that the positive relationship between innovation and performance is strongly backed by economic theory but the hypothetical mechanisms behind the link can vary. Investigating the nature of the connection is a promising line of future research and examining the parts of the CIS database that were largely neglected in CDM-type studies to date can help resolve the puzzle.